PENINGKATAN KUALITAS KOMPETENSI GURU BK SEBAGAI KONSELOR DI SEKOLAH DALAM MENGHADAPI TANTANGAN GLOBAL - Zaini Dahlan (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The counselor's knowledge competence includes knowledge of What is a counselor's supervisor, the requirements for a counselor's supervisor, the counselor's principal duties, the counselor's supervisory function, and the right and authority of a counselor's supervisor. Personality competence is the ability, skill and skill that a person displays. Foker states that